Construction and identification adenovirus of SOCS3. (12th October 2011) - Xiao, Liang; Ming, He; Tao, Chen; Zhiyan, Hui; Yuliang, Wu
Abstract : Objective: To construct and identify the recombinant adenovirus containing SOCS3, detect SOCS3 expression level in HEK293 cells and provide valuable reference for gene therapy of myocarditis. Methods: The SOCS3 gene was cloned by RT-PCR after total RNA extracted from peritoneal macrophage of rat, then subcloned with shuttle plasmid pAdtrack-CMV containing GFP reporter gene. PAdeasy-1 adenovirus system was used for co-transfecting shuttle plasmid and frame plasmid to Bj5183 cells. Reconstructed adenovirus was transfected to HEK293 cell after linearisation and mRNA and protein level of SOCS3 in the cell were detected. Results: SOCS3 gene was cloned and recombinant adenovirus pAd-SOCS3-GFP was constructed successfully through pAdeasy-1 system. After linearisation, recombinant adenovirus was transfected to HEK293 cell and the mRNA and protein level of SOCS3 in the cell were both significantly increased. Conclusion: Recombinant SOCS3 adenovirus has been constructed successfully and could be used for transfection in vivo or in vitro to treat inflammatory disease, for example, myocarditis.